Kinematic Changes in a Mouse Model of Penetrating Hippocampal Injury and Their Recovery After Intranasal Administration of Endometrial Mesenchymal Stem Cell-Derived Extracellular Vesicles - León-Moreno, Lilia Carolina; Castañeda-Arellano, Rolando; Aguilar-García, Irene Guadalupe; Desentis-Desentis, María Fernanda; Torres-Anguiano, Elizabeth; Gutiérrez-Almeida, Coral Estefanía; Najar-Acosta, Luis Jesús; Mendizabal-Ruiz, Gerardo; Ascencio-Piña, César Rodolfo; Dueñas-Jiménez, Judith Marcela; Rivas-Carrillo, Jorge David; Dueñas-Jiménez, Sergio Horacio (Frontiers in Cellular Neuroscience, 2020)
Locomotion speed changes appear following hippocampal injury. We used a hippocampal penetrating brain injury mouse model to analyze other kinematic changes. We found a significant decrease in locomotion speed in both the open field and tunnel walk tests. We described a new quantitative method that allows us to analyze and compare the displacement curves between mice steps. In the tunnel walk, we marked mice with indelible ink on the knee, ankle, and metatarsus of the left and right hindlimbs to evaluate both in every step. Animals with hippocampal damage exhibit slower locomotion speed in both hindlimbs. In contrast, in the cortical injured group, we observed significant speed decrease only in the right hindlimb. We found changes in the displacement patterns after hippocampal injury. Mesenchymal stem cells-derived extracellular vesicles had been used for the treatment of several diseases in animal models. This study evaluated the effects of intranasal administration of endometrial mesenchymal stem cells-derived extracellular vesicles on the outcome after the hippocampal injury. We report the presence of VEGF, GM-CSF, and IL-6 in these vesicles. We observed locomotion speed and displacement pattern preservation in mice after vesicle treatment. These mice had lower pyknotic cells percentage and a smaller damaged area in comparison with the non-treated group, probably due to angiogenesis, wound repair, and inflammation decrease. Our results build upon the evidence of the hippocampal role in walk control and suggest that the extracellular vesicles confer neuroprotection to the damaged hippocampus.